Evaluation of Primary Macro Nutrients on Arboretum Area in Lampung University Campus, Gedong Meneng - Afrianti, Nur Afni; Syam, Tamaluddin (UNIVERSITY OF LAMPUNG, 2014)
Vegetation has a strong influence on soil characteristics. Vegetation can contribute organic matter sand nutrients to the soil. This study aimed to assess soil fertility through various approaches physical and chemical soil on various types of cover crop in theÂ arboretum area at University of Lampung, and determined the type of cover crop that had the best effect on soil fertility. The research was be conducted by a survey method, which made observations on the soil characteristics of six species of cover crops following were rosewood (Dalbergia latifolia), teak (Tectona grandis), albizia (Paraserianthes Albiziaria), acacia (Acasia mangium), fern tree (Filicium desipiens), and mahogany (Swietenia macrophylla King). Soil characteristics observed data were the physical and chemical properties, obtained by field observations, through boring profiles and soil sampling. The results showed that soil fertility on rosewood, albizia, acacia and mahogany on campus area of Lampung University had contents of soil organic C, organic matter, and soil total N higher than teak and Fern tree. Litter from Rosewood, Albizia, and acacia had the best effect on soil fertility, so they could be the best covered vegetation to improve soil characteristics related to optimal and sustainable of land management.Keyword : Acacia, albizia, arboretum, cover crop, fern tree, litter, macronutrient, mahogany, rosewood, teak, and vegetation. [How to Cite: Nur AA and T Syam. 2014. Evaluation of Primary Macro Nutrients on Arboretum Area in Lampung University Campus, Gedong Meneng. J Trop Soils 19(2): 101-107. Doi: 10.5400/jts.2014.19.2.101]Â Â